(untitled) (World Bulletin of Social Sciences, 2023)
The article investigates the researches of scientists, who conducted scientific researches on the speeches of sale staff. There are many functions of language, all of which are embodied in the expression of thought. Through language and through the different means in it, different goals are realized. Through the language and a number of its functions, various buying and selling works are carried out on the street, in the surroundings and, especially in the market.